Web design with Macromedia Studio MX 2004 - Hunley, Eric (Charles River Media, 2004)
Web Design with Macromedia Studio MX 2004 provides beginning designers with a step-by-step process for creating a Web site with the new Macromedia Studio MX 2004. Structured around a good Web development cycle of plan, design, build, test, and maintain, the book starts by planning the site and creating a wire frame with Freehand MX, along with vector graphics for use in Macromedia Flash MX 204 and Fireworks MX 2004. From there it moves to Flash, where the designer learns how to create dynamic content for use on the Web. Next, Fireworks is used to manipulate graphics and create Web page designs. Then the content is brought into Dreamweaver MX 2004 and the site is launched. Throughout the book, the focus is not only on how to use each tool, but how to use them together to create a seamless workflow. The site used to illustrate these concepts and tools is not a sample site, but an actual live photography store Web site (www.jdukesphoto.com). All of the tools needed to create and test the Web site are on the book's CD-ROM, including trial versions of the Macromedia products covered in the book, as well as the Open Source server Technologies (Apache, MySQL, PHO, and PERL)